International Textbooks Analysis Used for EFL Students: A Critical Content Analysis of Multicultural from Kachru’s Models - Reni Puspitasari Dwi Lestariyana; Joko Nurkamto (Journal of Innovation in Educational and Cultural Research, 2022)
This study examines the multicultural contents in two international textbooks entitled New Interchange Fifth Edition used in Indonesia for English foreign language (EFL) students to underlying the multicultural values. Applying Kachru and Nelson’s model of English and their categorization into Inner, Outer and Expanding circles. This study also implemented both quantitative and qualitative analysis. The quantitative analysis refers to the quantitative data and to what extent multicultural values of race/ethnicity, gender/sexuality, social class, and people with are represented. The result showed that the representation of culture from three circles countries were unbalanced and stereotypical. The percentage shows from materials representation of inner, outer and expanding circles were 74,1 %, 23,3 % and 2,6% respectively. There were highly dominated inner circle culture even though these textbooks are used in expanding circles (e.g., Indonesia). Anchored from the research finding, it suggest that both textbook writers and designers should emphasized on balance multicultural values in international textbook materials particularly in expanding circle country (e.g. Indonesia) in order to help students recognize the cultural diversity.